Two-photon-assisted polymerization and reduction : emerging formulations and applications - Lay, Chee Leng (2020)
Two-photon lithography (TPL) is an emerging approach to fabricate complex multifunctional micro/nanostructures. This is because TPL can easily develop various 2D and 3D structures on a variety of surfaces, and there has been a rapidly expanding pool of processable photoresists to create different materials. However, challenges in developing two-photon processable photoresists currently impede progress in TPL. In this review, we critically discuss the importance of photoresist formulation in TPL. We begin by evaluating the commercial photoresists to design micro/nanostructures for promising applications in anti-counterfeiting, superomniphobicity, and micromachines with movable parts. Next, we discuss emerging hydrogel/organogel photoresists, focusing on customizing photoresist formulations to fabricate reconfigurable structures that can respond to changes in local pH, solvent, and temperature. We also review the development of metal salt-based photoresists for direct metal writing, whereby various formulations have been developed to enable applications in online sensing, catalysis, and electronics. Finally, we provide a critical outlook and highlight various outstanding challenges in formulating processable photoresists for TPL.